Efficient, energy-saving and environment-friendly synthesis method of copper-doped mesoporous silica solid acid catalyst
By rapidly doping copper elements at room temperature by solid-phase ball milling method, the high energy consumption, long reaction time and environmental pollution problems of copper-doped mesoporous silicon oxide molecular sieve materials in the prior art are solved, and the synthesis of high-efficiency, environmentally friendly and low-cost copper-doped mesoporous silicon oxide solid acid catalyst is achieved.
Patent Information
- Application Number
- CN202411890326.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art has problems such as high energy consumption, long reaction time, high equipment cost, environmental pollution, and low copper salt utilization and doping rates when preparing copper-doped mesoporous silicon oxide molecular sieve materials.
The solid-phase ball milling method is used to react soluble copper salt with mesoporous silica in a ball milling tank, and then dried in a blow drying box to achieve rapid and efficient doping of copper elements in the mesoporous silica framework.
This method shortens the traditional reaction time to 5-10 minutes, the copper salt utilization rate reaches 100%, the doping rate can reach 19.22%, the specific surface area is between 602-866cm2/g, and the process is simple, environmentally friendly and low-cost.
Smart Images

Figure CN119702051A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of inorganic non-metallic materials, and specifically relates to a mesoporous silica molecular sieve, and in particular to a highly efficient, energy-saving and environmentally friendly synthesis method of a copper-doped mesoporous silica solid acid catalyst. Background Art
[0002] Mesoporous silica materials have shown important application value in the fields of selective adsorption and separation, heterogeneous catalysis, drug loading and release, and new nanomaterials due to their large specific surface area, regular pore size distribution (2-50nm), and easily functionalized mesoporous walls, and have become a hot research material in recent years. However, the lack of active sites in unfunctionalized mesoporous silica limits its application in the above fields. Transition metal-doped mesoporous silica can produce high-density chemically active sites and acidic centers, which can provide an ideal place for the catalytic reaction in which molecules participate, making it show good catalytic activity.
[0003] In recent years, Cu-doped mesoporous silica has been used for phenol hydroxylation and degradation of organic pollutants because the chemically active sites Cu (II) in its skeleton can efficiently activate H2O2 to produce hydroxyl radicals. At present, the synthesis method of highly ordered high-acid active site copper-doped mesoporous silica is mainly a step-by-step synthesis method. For example, the patent CN109046439B "A Synthesis Method of a High-doping High-acid Mesoporous Silica Solid Acid Catalyst" applied by the inventor in the early stage uses acetate to promote the doping of copper elements in the mesoporous silica skeleton to prepare a copper-doped solid acid catalyst. However, this method requires ethanol as a dispersant, and the copper salt utilization rate (45%) and doping rate (13.9%) are low, resulting in high costs; and it is necessary to react at 70-80°C for 14-16h, and naturally cool to room temperature after the reaction is completed. The product is filtered, washed, and dried to obtain a powdery substance, which is heated to 480-550°C at a rate of 1-2°C / min and calcined for 4-6h to finally obtain a copper-doped mesoporous silica molecular sieve. This synthesis process not only produces wastewater containing Cu, polluting the environment, but also has poor safety, high technical difficulty, high equipment cost, long cycle, and is time-consuming and energy-consuming. Invention patent CN115646531B "A rapid energy-saving synthesis method for copper-doped mesoporous silica with high acidic active sites" uses microwave-assisted method to promote the doping of copper elements in the mesoporous silica skeleton, increasing the utilization rate of copper salt to 80-90% and the doping rate to 17.01%, reducing energy consumption (85-100°C) and reaction time (0.5-1h), but this method has high equipment requirements, high operation difficulty, and is difficult to mass produce; and it does not solve the problem of environmental pollution, and still produces wastewater containing Cu, and energy consumption and reaction time still need to be further reduced.
[0004] By searching the existing technologies at home and abroad, there is no literature reporting the use of solid phase ball milling to promote the doping of copper elements in the mesoporous silica skeleton, nor is there any literature reporting a method for synthesizing a copper-doped mesoporous silica solid acid catalyst with a copper salt utilization rate of 100%, low energy consumption (room temperature reaction), short time (5-10 minutes), simple process, and environmental protection (no wastewater generation). Summary of the invention
[0005] In view of various problems existing in the existing methods for preparing copper-doped mesoporous silica molecular sieve materials, the purpose of the present invention is to provide a highly efficient, energy-saving and environmentally friendly synthesis method of a copper-doped mesoporous silica solid acid catalyst.
[0006] In order to achieve the above technical purpose, the inventors have combined their years of research experience on mesoporous silica molecular sieves, conducted a large number of experimental studies and made unremitting efforts, and finally obtained the following technical solution: a highly efficient, energy-saving and environmentally friendly synthesis method of a copper-doped mesoporous silica solid acid catalyst, the method comprising the following steps:
[0007] (1) dissolving a soluble copper salt in water in a ball mill, adding mesoporous silica and a ball milling medium, and ball milling at a rate of 200 to 400 rpm for 5 to 10 min to obtain a viscous mixture;
[0008] (2) placing the viscous mixture in a forced air drying oven, heating it to 70-80° C., and drying it for 6-8 hours to obtain copper-doped mesoporous silica.
[0009] Further preferably, in the efficient, energy-saving and environmentally friendly synthesis method of the copper-doped mesoporous silica solid acid catalyst as described above, the mass ratio of the soluble copper salt to the mesoporous silica is (0.01-0.8):1.
[0010] Further preferably, in the above-mentioned efficient, energy-saving and environmentally friendly synthesis method of the copper-doped mesoporous silica solid acid catalyst, the mass ratio of the mesoporous silica to the ball milling medium is 1:(1-3).
[0011] Further preferably, in the above-mentioned efficient, energy-saving and environmentally friendly synthesis method of copper-doped mesoporous silica solid acid catalyst, the ratio of mesoporous silica to water is 1 g: (10-20) mL.
[0012] Further preferably, in the efficient, energy-saving and environmentally friendly synthesis method of the copper-doped mesoporous silica solid acid catalyst as described above, the soluble copper salt is selected from one or more of the following: copper chloride, copper sulfate, copper acetate, and copper nitrate.
[0013] Further preferably, in the efficient, energy-saving and environmentally friendly synthesis method of the copper-doped mesoporous silica solid acid catalyst as described above, the mesoporous silica is selected from any one of the following: SBA-15, MCM-41, FDU-5, KIT-6, HMS, MSU.
[0014] Further preferably, in the above-mentioned efficient, energy-saving and environmentally friendly synthesis method of copper-doped mesoporous silica solid acid catalyst, the ball milling medium is zirconia balls.
[0015] Still further preferably, in the highly efficient, energy-saving and environmentally friendly synthesis method of the copper-doped mesoporous silica solid acid catalyst as described above, the particle size of the zirconium oxide balls is 1.5 to 2.5 mm.
[0016] Further preferably, in the above-mentioned efficient, energy-saving and environmentally friendly synthesis method of copper-doped mesoporous silica solid acid catalyst, the heating rate in step (2) is 1-2° C. / min.
[0017] Further preferably, in the above-mentioned efficient, energy-saving and environmentally friendly synthesis method of copper-doped mesoporous silica solid acid catalyst, the copper doping rate of the copper-doped mesoporous silica obtained in step (2) is 0-19.22%, the copper salt utilization rate is 100%, and the specific surface area is 602-866 cm 2 / g.
[0018] Compared with the prior art, the method for synthesizing the copper-doped mesoporous silica solid acid catalyst according to the present invention has the following technical effects:
[0019] (1) The method of the present invention realizes the rapid and efficient doping of copper elements into the mesoporous silica skeleton through solid phase ball milling, shortening the traditional reaction time of 24 hours to 5-10 minutes. The reaction is carried out at room temperature and pressure, saving time and energy, requiring low equipment, and having a simple process flow and easy mass production.
[0020] (2) The method of the present invention realizes controllable adjustment of the doping amount of copper element in the mesoporous silicon oxide skeleton, the Cu / Si atomic ratio is 0 to 0.238, and the copper doping rate (copper molar percentage) is 0 to 19.22%.
[0021] (3) The method of the present invention omits the product filtration and washing process, which not only simplifies the process but also avoids the generation of Cu ion wastewater, is more environmentally friendly, and the copper salt utilization rate can reach 100%.
[0022] (4) The processing process of the present invention is simple, controllable, energy-saving, time-saving and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the small angle XRD pattern of the copper-doped SBA-15 mesoporous material in Example 1 of the present invention;
[0024] Figure 2 This is a wide-angle XRD pattern of the copper-doped SBA-15 mesoporous material in Example 1 of the present invention;
[0025] Figure 3 TEM image of copper-doped SBA-15 mesoporous material in Example 1 of the present invention;
[0026] Figure 4 The nitrogen adsorption and pore size distribution of the copper-doped SBA-15 mesoporous material in Example 1 of the present invention;
[0027] Figure 5 This is a solid ultraviolet absorption spectrum of copper-doped SBA-15 mesoporous material in Example 1 of the present invention;
[0028] Figure 6 This is the NH3-TPD chemical adsorption diagram of the copper-doped SBA-15 mesoporous material in Example 1 of the present invention;
[0029] Figure 7 This is the NH3-TPD chemical adsorption diagram of the copper-doped MCM-41 mesoporous material in Example 2 of the present invention;
[0030] Figure 8 This is the NH3-TPD chemical adsorption diagram of the copper-doped KIT-6 mesoporous material in Example 3 of the present invention;
[0031] Fig. 9 This is the wide-angle XRD pattern of the product obtained in Comparative Example 1;
[0032] Fig.10 This is the small angle XRD pattern of the product obtained in Comparative Example 2;
[0033] Fig.11 This is the TEM image of the product obtained in Comparative Example 2.
[0034] Fig.12 This is the TEM image of the product obtained in Comparative Example 2. DETAILED DESCRIPTION
[0035] Below in conjunction with embodiment, technical scheme of the present invention is clearly and completely described, the following examples are only used to illustrate the present invention, and should not be regarded as limiting the scope of protection of the present invention. In addition, those who do not indicate specific technical operation steps or conditions in the embodiments are all carried out according to the technology or conditions described in the documents in this area or according to the product specification. Those who do not indicate the manufacturer of reagents or instruments used are all conventional products that can be obtained by commercial purchase.
[0036] Example 1 Preparation of copper-doped mesoporous silicon oxide molecular sieve material:
[0037] Dissolve 0.8g of copper acetate monohydrate in 20mL of water in a ball mill, repeat the operation, and prepare 6 portions of copper acetate solution. Then weigh 1.0g of SBA-15, MCM-41, FDU-5, KIT-6, HMS and MSU respectively and disperse them in the copper acetate solution, add 1.0g of zirconia balls to each, and mill at 400 rpm for 5min to obtain a blue viscous mixture. Place the obtained viscous mixture in a forced air drying oven, heat it to 80℃ at a heating rate of 2℃ / min, and dry it for 8h to obtain blue copper-doped mesoporous silica.
[0038] The composition, mesoporous structure and microstructure of the prepared copper-doped SBA-15 mesoporous molecular sieve material are analyzed and characterized by XRD, high-temperature calcination, TEM, physical adsorption, solid UV, ICP-OES and chemical adsorption analysis.
[0039] (1) Mesoporous structure analysis (small angle XRD, TEM and physical adsorption)
[0040] like Figure 1 As shown in FIG. 1 , it is an X-ray powder diffraction pattern of the obtained copper-doped SBA-15 mesoporous molecular sieve material, in which characteristic diffraction peaks of (100), (110), and (200) crystal planes appear in the low angle range of 0.5-4°, indicating that a highly ordered two-dimensional hexagonal mesostructure is synthesized; Figure 2 From the wide-angle XRD pattern, it can be seen that the product does not form CuO impurities; the blue color remains unchanged after calcination at 550°C for 6 hours in a muffle furnace, indicating that Cu has entered the skeleton structure of SBA-15.
[0041] like Figure 3 As shown, it is a TEM image of copper-doped SBA-15 mesoporous molecular sieve material. It can be seen from the figure that it has regular hexagonal pores in the vertical pore direction, where the black shadows show the pore walls and the white represents the pores. No oxide particles are formed in or outside the pores.
[0042] like Figure 4 As shown, it is the nitrogen adsorption and pore size distribution of copper-doped SBA-15 mesoporous molecular sieve material, with a specific surface area of 602 cm 2 / g. It can be seen from the figure that the N2 adsorption / desorption isotherm is a typical IV type curve with an H1 hysteresis loop, which is caused by the capillary condensation of N2 molecules in the mesopores. This shows that the pore size distribution of the sample is narrow and uniform, which is consistent with the pore size distribution results. The average pore size is 6.4nm.
[0043] (2) Solid UV absorption spectroscopy (UV-vis DRS) and ICP analysis
[0044] like Figure 5As shown in the figure, it is a solid ultraviolet absorption spectrum of copper-doped SBA-15 mesoporous molecular sieve material. In the figure, an ultraviolet absorption peak appears between 200-300nm, which can be classified as the signal of tetrahedral coordinated Cu species doped in the framework, indicating that the Cu element is doped in the framework structure. From ICP-OES analysis, it can be seen that Cu / Si=0.238, the doping rate is 19.22%, and the copper salt utilization rate can reach 100%.
[0045] (3) NH3-TPD chemical adsorption analysis
[0046] like Figure 6 As shown, it is the NH3-TPD chemical adsorption diagram of copper-doped SBA-15 mesoporous molecular sieve material. According to the NH3-TPD results of copper-doped SBA-15, a strong NH3 desorption peak appeared near 200°C, proving the formation of Cu-O-Si bonds and the generation of high-density acid active sites, indicating that the Cu element was successfully doped into the skeleton structure of SBA-15 to form a solid acid catalyst.
[0047] Copper-doped MCM-41, FDU-5, KIT-6, HMS and MSU mesoporous silica molecular sieve materials were characterized by XRD, SEM, TEM, ICP-OES, solid UV, physical adsorption and chemical adsorption analysis, respectively, indicating that Cu-doped mesoporous silica: Cu-MCM-41, Cu-FDU-5, Cu-KIT-6, Cu-HMS and Cu-MSU mesoporous molecular sieve materials were successfully prepared.
[0048] In summary, the present invention successfully prepares a highly ordered copper-doped mesoporous silica solid acid catalyst with high acidic active sites.
[0049] Example 2 Preparation of copper-doped mesoporous silicon oxide molecular sieve material:
[0050] Dissolve 0.55g of copper acetate monohydrate in 18mL of water in a ball mill, repeat the operation, and prepare 6 portions of copper acetate solution. Then weigh 1.0g of SBA-15, MCM-41, FDU-5, KIT-6, HMS and MSU respectively and disperse them in the copper acetate solution, add 1.0g of zirconia balls to each, and mill at 350 rpm for 8min to obtain a blue viscous mixture. Place the obtained viscous mixture in a forced air drying oven, heat it to 70℃ at a heating rate of 1℃ / min, and dry it for 8h to obtain blue copper-doped mesoporous silica.
[0051] The products were characterized by XRD, TEM, ICP-OES, solid UV, physical adsorption and chemical adsorption analysis, indicating that the copper-doped mesoporous silica molecular sieve materials with a Cu / Si ratio of about 0.164 were successfully prepared: Cu-MCM-41, Cu-SBA-15, Cu-FDU-5, Cu-KIT-6, Cu-HMS and Cu-MSU. At the same time, no copper oxide was found in the prepared products. All of the above materials produced acid active sites. Figure 7 As shown, it is the NH3-TPD chemical adsorption diagram of copper-doped MCM-41 mesoporous molecular sieve material. It can be seen from the figure that a strong NH3 desorption peak appears near 200°C, proving the formation of Cu-O-Si bonds and the generation of acid active sites, indicating that the Cu element is successfully doped into the skeleton structure of MCM-41 to form a solid acid catalyst.
[0052] In summary, the present invention successfully prepares a copper-doped highly ordered mesoporous silica solid acid catalyst.
[0053] Example 3 Preparation of copper-doped mesoporous silicon oxide molecular sieve material:
[0054] Dissolve 0.34g of copper acetate monohydrate in 10mL of water in a ball mill, repeat the operation, and prepare 6 portions of copper acetate solution. Then weigh 1.0g of SBA-15, MCM-41, FDU-5, KIT-6, HMS and MSU respectively and disperse them in the copper acetate solution, add 1.0g of zirconia balls to each, and mill at 260 rpm for 6min to obtain a blue viscous mixture. Place the obtained viscous mixture in a forced air drying oven, heat it to 75℃ at a heating rate of 1.5℃ / min, and dry it for 9h to obtain blue copper-doped mesoporous silica.
[0055] The products were characterized by XRD, TEM, ICP-OES, solid UV, physical adsorption and chemical adsorption analysis, indicating that the copper-doped mesoporous silica molecular sieve materials with a Cu / Si ratio of about 0.102 were successfully prepared: Cu-MCM-41, Cu-SBA-15, Cu-FDU-5, Cu-KIT-6, Cu-HMS and Cu-MSU. At the same time, no copper oxide was found in the prepared products. All of the above materials produced acid active sites. Figure 8 As shown, it is the NH3-TPD chemical adsorption diagram of copper-doped KIT-6 mesoporous molecular sieve material. It can be seen from the figure that a strong NH3 desorption peak appears near 200°C, proving the formation of Cu-O-Si bonds and the generation of acid active sites, indicating that the Cu element is successfully doped into the skeleton structure of KIT-6 to form a solid acid catalyst.
[0056] In summary, the present invention successfully prepares a copper-doped highly ordered mesoporous silica solid acid catalyst.
[0057] Comparative Example 1
[0058] The treatment process and parameters are the same as those of Example 1 of the present invention, except that the product is not ball-milled, and a blue product is obtained. However, a black product is obtained by calcining at 550°C for 6 h in a muffle furnace. Fig. 9 ) shows that CuO is formed, which indicates that Cu does not enter the framework structure of SBA-15 and no Cu-doped mesoporous silica molecular sieve material is formed.
[0059] Comparative Example 2
[0060] The treatment process and parameters are the same as those in Example 1 of the present invention, except that the ball milling reaction lasts for 12 min. A blue product is obtained. XRD ( Fig.10 ) and TEM( Fig.11 ) analysis shows that the mesoporous structure is destroyed and basically no obvious pore structure can be observed.
[0061] Comparative Example 3
[0062] The treatment process and parameters are the same as those in Example 1 of the present invention, except that the ball milling reaction was performed for 4 minutes, and a blue product was obtained. However, a gray and blue mixed product was obtained after calcination at 550°C in a muffle furnace for 6 hours, indicating that only part of the Cu entered the skeleton structure of SBA-15, and the remaining part of the Cu was not doped, resulting in the formation of CuO-loaded copper-doped mesoporous silica molecular sieve material after calcination at 550°C.
Claims
1. A highly efficient, energy-saving and environmentally friendly synthesis method of a copper-doped mesoporous silica solid acid catalyst, characterized in that: The method comprises the following steps: (1) dissolving a soluble copper salt in water in a ball mill, adding mesoporous silica and a ball milling medium, and ball milling at a rate of 200 to 400 rpm for 5 to 10 min to obtain a viscous mixture; (2) placing the viscous mixture in a forced air drying oven, heating it to 70-80° C., and drying it for 6-8 hours to obtain copper-doped mesoporous silica.
2. The highly efficient, energy-saving and environmentally friendly synthesis method of the copper-doped mesoporous silica solid acid catalyst according to claim 1, characterized in that: The mass ratio of the soluble copper salt to the mesoporous silicon oxide is (0.01-0.8):
1.
3. The highly efficient, energy-saving and environmentally friendly synthesis method of the copper-doped mesoporous silica solid acid catalyst according to claim 1, characterized in that: The mass ratio of the mesoporous silica to the ball milling medium is 1:(1-3).
4. The highly efficient, energy-saving and environmentally friendly synthesis method of the copper-doped mesoporous silica solid acid catalyst according to claim 1, characterized in that: The ratio of the mesoporous silica to water is 1 g: (10-20) mL.
5. The highly efficient, energy-saving and environmentally friendly synthesis method of the copper-doped mesoporous silica solid acid catalyst according to claim 1, characterized in that: The soluble copper salt is selected from one or more of the following: copper chloride, copper sulfate, copper acetate, and copper nitrate.
6. The highly efficient, energy-saving and environmentally friendly synthesis method of the copper-doped mesoporous silica solid acid catalyst according to claim 1, characterized in that: The mesoporous silica is selected from any one of the following: SBA-15, MCM-41, FDU-5, KIT-6, HMS, and MSU.
7. The highly efficient, energy-saving and environmentally friendly synthesis method of the copper-doped mesoporous silica solid acid catalyst according to claim 1, characterized in that: The ball milling medium is a zirconia ball.
8. The highly efficient, energy-saving and environmentally friendly synthesis method of the copper-doped mesoporous silica solid acid catalyst according to claim 7, characterized in that: The particle size of the zirconia balls is 1.5 to 2.5 mm.
9. The highly efficient, energy-saving and environmentally friendly synthesis method of the copper-doped mesoporous silica solid acid catalyst according to claim 1, characterized in that: The heating rate in step (2) is 1-2°C / min.
10. The highly efficient, energy-saving and environmentally friendly synthesis method of the copper-doped mesoporous silica solid acid catalyst according to claim 1, characterized in that: The copper doping rate of the copper-doped mesoporous silicon oxide obtained in step (2) is 0-19.22%, the copper salt utilization rate is 100%, and the specific surface area is 602-866cm 2 / g.
Citation Information
Patent Citations
A method for synthesizing a highly doped, highly acidic mesoporous silica solid acid catalyst
CN109046439B
A rapid and energy-efficient synthesis method for copper-doped mesoporous silica with highly acidic active sites.
CN115646531B